Combined effect of S-type lateral root development and localized P application for increasing P uptake of lowland rice - Njato Mickaël Rakotoarisoa; Yasuhiro Tsujimoto; Aung Zaw Oo; Yoshiaki Inukai; Mana Kano-Nakata; Hiroshi Ehara (Plant Production Science)
Both root morphology and fertilizer management play critical roles in increasing phosphorus (P) use efficiency. However, their interaction under flooded rice cultivation has been little understood. A mutant of our1 gene and its wild type, Kimmaze (WT), which show different lateral root development patterns, were grown in flooded pots after uniformly incorporating P (Pinco) or placing the same amount of P by spot (Ploc). The Ploc increased the initial P uptake and biomass of WT in greater degrees than our1. The positive combination of WT and Ploc is associated with the enhanced development of S-type lateral and nodal roots around the P-localized zone in the top and middle soil layers that did not occur for our1. The study implies that P fertilizer use efficiency can be improved further by combining localized P application and root phenotypes that can induce nodal and S-type lateral root development in the P-enriched zone.